The effects of contract-type mismatch and matching frictions on unemployment duration: Evidence for Portugal - Antonio Menezes; Dario Sciulli (Journal of Applied Economics, 2022)
This paper analyses the impact of matching frictions in the Portuguese labour market on individual unemployment hazard rates and unemployment durations. The coexistence of permanent contracts and temporary contracts in the Portuguese (dual) labour-market is akin to a matching friction, with a contract-type mismatch between jobseekers who prefer permanent contracts, whereas firms, in turn, prefer to offer temporary contracts. The paper uses a rich micro dataset which allows to compute a time and space varying contract-type mismatch index, over 86 local labour markets (job-centers of the Portuguese Public Employment System) and five years. Employing discrete time hazard models and a stock-flow matching mechanism, we find that local labour markets with higher contract-type mismatch rates are characterized by lower hazard rates and longer unemployment duration. Improving the desirability of temporary contracts and information about local contract-type mismatch rates may reduce matching frictions and average unemployment duration.
Keywords: 330; dual labour markets; matching frictions; stock-flow matching functions; survival analysis; Unemployment duration